2017
DOI: 10.20959/wjpps20178-9833
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Antimicrobial Activity of Quinoline Derivatives

Abstract: Quinoline family compounds are widely used as a parent compound to make drugs fungicides, biocides, alkaloids, dyes, rubber, chemicals, flavoring agents, antiseptic. Its derivatives are one of the important constituents of pharmacologically active synthetic compounds such as anti-inflammatory, antimicrobial agents, cytotoxic activity, antidotal, antibacterial and so on. The present work is done to explore the possibility of getting novel antimicrobial agents by linking 3-formyl-6-nitroquinoline-2-thione with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The reaction mixture was then refluxed for 7-9 hours before cooling to room temperature. The solid crude material was filtered and recrystallized from ethanol [17]. The physical properties of the title compounds 13-15 are listed in Table 1.…”
Section: Synthesis Of Oxazolidine-4-one Derivatives 13-15mentioning
confidence: 99%
“…The reaction mixture was then refluxed for 7-9 hours before cooling to room temperature. The solid crude material was filtered and recrystallized from ethanol [17]. The physical properties of the title compounds 13-15 are listed in Table 1.…”
Section: Synthesis Of Oxazolidine-4-one Derivatives 13-15mentioning
confidence: 99%
“…Firoz et al explored the novel quinolone derivatives and reported that compound 102 , was the most potent one as on 16th day the percentage wound contraction was 94% as compared to the 87%, 84.5% contraction of standard povidone‐iodine and control, respectively. Furthermore, at a concentration of 125 μg/ml this compound with hydrogen peroxide showed more antioxidant activity than the standard ascorbic acid with a percentage inhibition of 66.54% and 43.95%, respectively (Firoz et al, 2017). Savegnago and other coresearcher reported the synthesis and antioxidant activity of novel 4‐arylchalcogenyl‐chloroquinoline analogues.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The 1,2,4-triazole ring has been shown to have a wide range of pharmacological properties, including antibacterial and antifungal properties [19]. Meanwhile, thiazolidine-4one heterocycles exhibit various effects on health such as antimicrobial, antifungal, antitumor, antidiabetic, anti-inflammatory, gastrointestinal issues and several different methods of producing heterocycles through cyclization reactions have been discussed in the medical literature [20][21][22][23][24][25]. For example, thiazoles have been synthesized by cyclization of thiourea with acetic acid under alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%